The female leadership paradox : power, performance, and promotion - Visser, Mirella (Houndmills, Basingstoke, Hampshire : Palgrave MacMillan, 2011)
'The best-kept secret in corporate life is the vanishing act of women on their way to the top. Despite massive attention to the issue the number of women in top positions remains shockingly low. This book shows what women themselves can do to optimize their careers and how this can bring benefits to the companies and organizations they work for'--
Seven themes -- Personal leadership -- Pattern of power, performance, and promotion -- The female leadership paradox -- The power of frames -- Culture -- Power and politics -- Career -- Skills -- Strategic networking.
Includes index.
Keywords: Women -- Vocational guidance; Leadership in women; Women executives -- Promotions; Career development